Organosilicon Radicals with Si-H and Si-Me Bonds from Commodity Precursors - Kundu, Subrata; Samuel, Prinson P; Sinhababu, Soumen; Luebben, Anna V; Dittrich, Birger; Andrada, Diego M; Frenking, Gernot; Stückl, A Claudia; Schwederski, Brigitte; Paretzki, Alexa; Kaim, Wolfgang; Roesky, Herbert W (Journal of the American Chemical Society, 2017)
The cyclic alkyl(amino) carbene (cAAC) stabilized biradicals of composition (cAAC) SiH (1), (cAAC)SiMe -SiMe (cAAC) (2), and (cAAC)SiMeCl-SiMeCl(cAAC) (3) have been isolated as molecular species. All the compounds are stable at room temperature for more than 6 months under inert conditions in the solid state. All radical species were fully characterized by single-crystal X-ray structure analysis and EPR spectroscopy. Furthermore, the structure and bonding of compounds 1-3 have been investigated by theoretical methods. Compound 1 contains the SiH moiety and this is the first instance, where we have isolated 1 without an acceptor molecule.